The role of the Salmonella PagN protein in adhesion and invasion - Paré, Samantha E. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2015)
Salmonella, an important genus of Gram-negative enteric bacteria, is the causative agent of many different diseases including Typhoid Fever and Gastroenteritis. Salmonella utilises multiple methods of invading mammalian cells, the best characterised is the Type Three Secretion System (T3SS). In addition to the T3SS, Salmonella express a multitude of fimbrial and non-fimbrial adhesins to facilitate attachment to and invasion of the epithelial layer lining the intestinal mucosa.
Keywords: Clinical Microbiology, Ph.D.; Ph.D. Trinity College Dublin